Designing the building space of a shopping street to use as a disaster evacuation shelter during the COVID-19 pandemic: A case study in Kobe, Japan. (January 2022) - Yokomatsu, Muneta; Park, Hyejeong; Kotani, Hitomu; Ito, Hideyuki
Abstract: This study considers the risk of a natural hazard-induced disaster occurring during a pandemic, such as the novel coronavirus (COVID-19) pandemic, and develops the idea of utilizing a shopping street with disaster-proof buildings as a temporary evacuation shelter by incorporating countermeasures against the spread of infectious diseases. Using a case study of a shopping street in Kobe, Japan, we estimate shelter capacity by considering the requirement of 6 m 2 of space allotted for each person. The shelter can accommodate 1194 evacuees and provide them with food and drinks for one day, even in the worst case of lifeline disruption. This study proposes a method of designing shelter space, and demonstrates how non-homogeneous and noncontinuous spaces within shopping street buildings can be applied to prevent the spread of infection, through the classification of evacuee types and use of space and facilities designated for each type. The study further examines the liability issue of secondary infection at the shelter with reference to civic law and the roles of government in developing a distributed evacuation framework. Highlights: This study considers a plan of disaster evacuation during a pandemic. The idea of utilizing shopping-street buildings as a temporary shelter is extended. A shopping-street shelter in Kobe, Japan, can accommodate 1194 evacuees. A method of designing shelter space is shown with the classification of evacuees. The liability issue of secondary infection at the shelter is examined.